Intellectual measurement and evaluation of the results of customs authorities’ activities - G. I. Goremykina; Yu. E. Gupanova (Управление)
The new Strategy for the Development of the Customs Service of the Russian Federation until 2030 calls optimization and improvement of customs administration as one of its fundamental principles. The emerging trend leads to an increase in the obligatoriness of the development of formalized means of modeling and analysis of management processes in the customs sphere. Performance measurement is one of the most effective management tools. In this article, the authors, taking as a basis the basic provisions of the National Technological Initiative, continued mapping the problem of measuring the results of the customs authorities functioning in key areas of their activities in the context of the qualitological system transformation of the customs institution, due to the process of its intellectualization in the digital economy. The purpose of the study is to create a model for measuring the results of the customs authorities’ activities. To specify the general methodology, a model for measuring the degree of achievement the goal in the “Finance” direction is described. The study is based on a cognitive approach that allows describing the intellectual environment of customs authorities and models of evaluation and management based on fuzzy logic algorithms. The implementation of the technology for presenting experts’ knowledge in the subject area is carried out on the basis of constructing a prescriptive logical production model that allows formalizing expert knowledge in the form of implicative statements involving fuzzy formulations in antecedents and consequents, and using a generalized modus ponens as a logical conclusion. Computer development of a mathematical model is carried out in the Fuzzy Logic Toolbox for Matlab application software package.